The The Effect of Perceived Organizational Support and Job Crafting on The Organizational Citizenship Behavior Through Work Engagement as an Intervening Variable - Halimatus Sadiyah; Khoirur Rozaq; Dwiarko Nugrohoseno (Journal of Business and Management Review, 2023)
This research aims to examine and analyze the effect of perceived organizational support and job crafting on organizational citizenship behavior through work engagement as an intervening variable. Respondents in this study were the employees of companies engaged in the banking sector. The results of analysis and hypothesis testing by SmartPLS show that there is no effect between perceived organizational support on organizational citizenship behavior. Job crafting affects on organizational citizenship behavior. Perceived organizational support and job crafting affect work engagement. Work engagement affects mediating the relationship between perceived organizational support and job crafting on organizational citizenship behavior.